STAFF SUPERVISION AND DISCIPLINE IN A SCHOOL AS AN ORGANISATION - SHONHIWA, DOCTOR CAXTON (IJRDO- Journal of Educational Research, 2017)
The present paper discusses staff supervision and discipline in a school context. As we know, in order to maintain an efficient and effective work environment, employees are often required to address inappropriate behaviour and / or performance through corrective and / or disciplinary action. Supervision is a process by which a trained professional provides regular support, instruction and feedback to peer supporters. The process is designed to ensure the emotional well being of both the peer supporters and the clients accessing the program. The benefits of supervision include enhanced accountability, increased feeling of support, development of professional skills and improved efficiency. Supervision is also associated with decreased feelings of isolation and role ambiguity. The increased morale generated by supervision ultimately results in lower levels of volunteer burnouts. The supervisor being the manager in a direct contact with the operatives, has got multifarious functions to perform. The objective behind performance of these functions is to bring stability and soundness in the organisation which can be secured through increase in profits and better results which is an end result of higher productivity. Therefore, a supervisor needs to make sure that all his / her members of staff are well disciplined and focused at their core business all the time.